Defensa de territorios indígenas en las tierras bajas de Bolivia: derechos colectivos, neoextractivismo y autonomía - Pabel Camilo López Flores (e-cadernos ces)
Socioterritorial conflicts and movements in Bolivia have highlighted the ways infringe the collective rights of indigenous peoples have been infringed and seem to challenge and dispute the imaginary of societal/state change that emerged in this country in the past decade, such as the “pluri-nationality”, the “indigenous autonomies”, the “Living Well” and the “decolonization”. In several territories of Bolivia there are strong tensions, sometimes violent, between a vision of “development” and policies of expansion/intensification of extractivism by the State and the Government and, on the other hand, with demonstrations in defense of communitarian territorialities. I propose a problematization of the current situation in the so-called lowlands, where indigenous political subjects may be configuring social movements based on forms of territorial defense, perhaps, of a counter-hegemonic scope.